2007
DOI: 10.1108/02652320710739850
|View full text |Cite
|
Sign up to set email alerts
|

Why do Malaysian customers patronise Islamic banks?

Abstract: Purpose -The purpose of this paper is to examine the main factors that motivate customers to deal with Islamic banks particularly in a dual banking environment, like in the case of Malaysia. A discussion on factors relating to corporate social responsibility initiatives as part of potential customers' banking selection criteria is also included. Design/methodology/approach -The paper presents primary data collected by self-administered questionnaires involving a sample of 750 respondents from four different re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
153
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(176 citation statements)
references
References 27 publications
17
153
1
5
Order By: Relevance
“…It confirms that religion is an integrated process of values relative to the holly topics, while religiosity is perceived as the level to which beliefs are practiced by individual Islamic principles. The finding is consistent with the results reached by Dusuki and Abdullah (2007) who stated that Islamic bankers should no longer rely upon marketing strategy of attracting religious customers who might only concern about Islamicity of financial product. Erol and El-Bdour (1989) observed that religious causes are not the only item for inviting customers.…”
Section: Selection Criteriasupporting
confidence: 82%
See 1 more Smart Citation
“…It confirms that religion is an integrated process of values relative to the holly topics, while religiosity is perceived as the level to which beliefs are practiced by individual Islamic principles. The finding is consistent with the results reached by Dusuki and Abdullah (2007) who stated that Islamic bankers should no longer rely upon marketing strategy of attracting religious customers who might only concern about Islamicity of financial product. Erol and El-Bdour (1989) observed that religious causes are not the only item for inviting customers.…”
Section: Selection Criteriasupporting
confidence: 82%
“…Ahmad and Haron (2002) found that the major factors behind selecting IBs are religious motives, service charges, bank reputation and location. Dusuki and Abdullah (2007) confirmed that financial reputation and quality service offered by the bank are the main items of selecting IBs. observed that the majority of dealings with Islamic bank are satisfied with the overall service qualities.…”
Section: Literature Review and Previous Studiesmentioning
confidence: 63%
“…The results in Tables 5-6 indicate that customers of both Islamic and conventional banks are highly satisfied with the banks' competent personnel, friendliness and efficiency of service. The findings of this study concur well with those of Dusuki and Abdullah (2007) who found that personnel factor is one of the major factors influencing customers in making decision to patronize a particular bank. Abbas et al (2003) who conducted a study on customers' choice in selecting Islamic financing products reported that incompetence and lack of courtesy of Islamic bank's personnel was the main reason why customers averted Islamic finance.…”
Section: Ranking Of Customer Satisfactionsupporting
confidence: 82%
“…Among the common factors used to measure customer satisfaction are service delivery (fast and efficient), convenience (location and parking facilities). A study conducted by Dusuki and Abdullah (2007) on 52 different branches of Islamic banks in Malaysia found that customer satisfaction normally depends on the quality of services provided by Islamic banks. According to Dusuki and Abdullah (2007), the quality of services include factors such as treating customers politely and with respect; staff ability to uphold trust and confidence; effective and efficient in handling transactions; and competency of staff in handling customers banking needs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Various studies (for example, Naser et al, 1999;Almossawi, 2001;Dusuki & Abdullah, 2007;Gait & Worthington, 2008;Mansour et al, 2010) have affirmed that the reputation as of the important contributors in the selection of Islamic banking among customers. It is in line with a takaful study, which found that majority of respondents chose reputation as their reason for choosing takaful operator (Bashir et al, 2011).…”
Section: Reputation and Recommendationmentioning
confidence: 99%